Review on Social Media and Digital Security - Amar Yahya Hussien (Qubahan Academic Journal)
The emerging social media with inherent capabilities seems to be gaining edge over comprehensiveness, diversity and wisdom, nevertheless its security and trustworthiness issues have also become increasingly serious, which need to be addressed urgently. The available studies mainly aim at both social media content and user security, including model, protocol, mechanism and algorithm. Unfortunately, there is a lack of investigating on effective and efficient evaluations and measurements for security and trustworthiness of various social media tools, platforms and applications, thus has effect on their further improvement and evolution. To address the challenge, this paper firstly made a survey on the state-of-the-art of social media networks security and trustworthiness particularly for the increasingly growing sophistication and variety of attacks as well as related intelligence applications. And then, we highlighted a new direction on evaluating and measuring those fundamental and underlying platforms, meanwhile proposing a hierarchical architecture for crowd evaluations based on signaling theory and crowd computing, which is essential for social media ecosystem. Finally, we conclude our work with several open issues and cutting-edge challenges.